Public Expenditure and Financial Accountability Assessment : Federal Democratic Republic of Ethiopia (Southern Nations, Nationalities and Peoples Region) - World Bank (World Bank, Washington, DC, 2020)
The objective of the Public Expenditure and Financial Accountability (PEFA) assessment is to review the current performance of the public financial management (PFM) systems, processes, and institutions of the Southern Nations, Nationalities, and Peoples’ Region (SNNPR). The assessment is aimed at assisting the government in identifying PFM weaknesses that may inhibit effective delivery of services to its citizens and the realization of its development objectives in general. Furthermore, the findings of the PEFA assessment will assist the government in refining the PFM reform strategy that it has already developed and provide the basis for a coherent PFM reform program that can be supported by development partners (DPs), as well as through the government’s own initiatives. The regional PEFA assessment covered regional government budgeted units, the Office of Federal Auditor General (OFAG), and Parliament. The assessment shows the state of PFM performance of the region at the time of the fieldwork in November 2019.